Agronomic Performance of Perennial Grain Genotypes in the Palouse Region of the Pacific Northwest, USA - Clark, Ian; Jones, Stephen S.; Reganold, John P.; Sanguinet, Karen A.; Murphy, Kevin M. (Frontiers in Sustainable Food Systems, 2019)
Annual plants are currently the dominant growth habit for grain production systems but often create agroecosystems with negative environmental consequences. Developing grains with a perennial growth habit provides an opportunity to produce staple crops in a more environmentally beneficial manner. Amphiploids of perennial tall wheatgrass (Thinopyrum elongatum) and common annual wheat (Triticum aestivum) have been produced for wheat-like traits while exhibiting post-sexual cycle regrowth (PSCR). Here we report results from two experiments at two locations in the Palouse region of the U.S. Pacific Northwest (PNW) designed to (1) evaluate a subset of the current perennial grain germplasm base and (2) test post-harvest management strategies on key perennial growth habit traits. The first experiment evaluated 18 putative perennial amphiploid lines, two annual wheat varieties, and one intermediate wheatgrass variety (Thinopyrum intermedium) for yield, PSCR, key agronomic traits, and grain quality characteristics. Results from this trial showed mean yields ranged from 713 to 2874 kg/ha among the amphiploids and 1627 to 6867 kg/ha with the annual wheat varieties. Variation across the amphiploids was found for key agronomic and quality traits, indicating potential for continued selection and improvement. When compared to the two annuals, the four highest-yielding amphiploids produced the same yield at one location but 50 to 60% less at the other. Regarding grain qualities, amphiploids had lower test weights and thousand kernel weights, smaller kernel diameters, lower starch content, and higher protein, ash, and fiber. The second experiment investigated the effect of post-harvest residue management on PSCR and winter survival of two amphiploids using mowing, burning, and a control. Mowing the residue and PSCR significantly increased winter survival across both amphiploids at one location from 3% in the control to 63% in the mowed treatment. Burning the residue did not improve survival. Our results address three important challenges in perennial grain development in the Palouse region: selecting a stable perennial habit, increasing grain yield, and improving marketable grain quality traits. Each of these challenges will require significant research efforts by plant breeders and agronomists prior to widespread adoption of perennial grains in the Palouse region of the PNW.